2nd Charles Richet et Jules Héricourt Workshop: Therapeutic antibodies and anaphylaxis; May 31–June 1, 2011; Tours, France - Daguet, Arnaud (Landes Bioscience, 2011)
The Charles Richet and Jules Héricourt workshops honor the memory of Jules Héricourt (1850–1938) and Charles Richet (1850–1935) who described the principle of serotherapy in 1888 and made the very first attempts to fight cancer with serotherapy in 1895. In 1902, Charles Richet and Paul Portier described “anaphylaxis,” a discovery awarded the Nobel Prize in 1913. The first workshop, “Towards the clinical use of monoclonal antibodies with higher cytolytic efficacy in cancer” was held in Tours, France on November 20–21, 2008. The second Charles Richet and Jules Héricourt workshop, held May 31–June 1, 2011 at the University of Tours, France, was also organized by the Cancéropôle Grand Ouest. The topic of the workshop was therapeutic antibodies and anaphylaxis, a subject rarely addressed in congresses focused on mAbs. To have discussions about mAb side effects with complete objectivity, the congress was organized independently of any sponsorship from pharmaceutical companies. This academic event was motivated by the high incidence of shocks to cetuximab and the need to compile and evaluate scattered information. This growing public health concern was thus analyzed from different scientific and medical angles. The first session was devoted to acute infusion reactions, with an emphasis on deconvolution of the terms “cytokine-release syndrome,” “cytokine storms,” “anaphylaxis” and their epidemiology. This session concluded with the Charles Richet lecture on cetuximab anaphylaxis and anti-αGal IgE by Thomas Platts-Mills, its discoverer. In the next session, the involvement of anti-glycan antibodies in both anaphylaxis and delayed hypersensitivity reactions to therapeutic antibodies was discussed. A gala dinner was held in the gardens of the beautiful château of Villandry, which was acquired and restored by Joachim Carvalho, a pupil of Charles Richet's and great-grandfather of the present owner. The final session focused on strategies to prevent cetuximab anaphylaxis in clinical practice included a variety of topics, e.g., premedication, biobetters and biosimilars, skin testing and predictive assays. All speakers and attendees enjoyed this very stimulating and rewarding meeting, which gathered many people with divergent scientific backgrounds and medical specialties.